COVID-19 mortality associated with multidimensional poverty, ethnicities, and armed conflict in Colombia: retrospective observational study based on national records - Claudia Inés Birchenall-Jiménez; Claudia Inés Birchenall-Jiménez; Wilson Giovanni Jiménez-Barbosa; Javier Riascos-Ochoa; Federico Cosenz (Frontiers in Public Health)
BackgroundThe COVID-19 pandemic in Colombia exposed the interplay between multidimensional poverty, ethnic diversity, and armed conflict. This crisis worsened inequalities, disproportionately affecting Afro-Colombian and Indigenous communities already living in adverse conditions. Armed conflict further weakened social capital, limiting wellbeing in impoverished and violent regions. This study aimed to investigate the associations of poverty, ethnicity, and conflict zones with COVID-19 mortality.MethodsA retrospective observational study based on national records was conducted in Colombia from March 2020 to December 2022, in which COVID-19 cases confirmed by PCR or antigen tests were analyzed. Demographic, ethnic, and mortality data were obtained from the National Institute of Health, while poverty data were obtained from the DANE's 2018 census. Descriptive analyses, chi-square tests, and bivariate analyses were performed. A multilevel logistic regression model identified risk factors, reporting odds ratios (ORs) with 95% confidence intervals (CIs).ResultsBetween March 2020 and December 2022, 6,313,872 COVID-19 cases were recorded in Colombia. Afro-Colombians 2.58% and Indigenous peoples (2.75%) had higher mortality than White/Mestizo individuals did (2.24%). ZOMAC municipalities reported a mortality rate of 3.61%, and PDET municipalities reported a mortality rate of 3.20%. Multilevel analysis revealed increased mortality risks for Afro-Colombians (OR 1.14, 95% CI 1.11–1.18), Indigenous peoples (OR 1.22, 95% CI 1.17–1.28), and residents of ZOMAC (OR 1.69, 95% CI 1.66–1.72) and PDET municipalities (OR 1.34, 95% CI 1.44–1.49).ConclusionsThis study highlights disparities in COVID-19 mortality influenced by ethnic, socioeconomic, and territorial factors, with a greater burden on Afro-Colombians, Indigenous peoples, and conflict zones. Public health policies must address these structural inequalities.